Characteristic features of attention of athletes, as an indicator of mental disability - Гант, О. Є.; Долиновська, О. Н. (Slobozhanskyi Herald of Science and Sport, 2011)
It is established that the restriction of the volume of voluntary attention and decrease its function in athletes, in terms of competitive activity, are functional in nature and amenable to reduction in post competitive period.